EPID-14. HISPANIC ETHNICITY AND SOCIOECONOMIC STATUS ARE INDEPENDENTLY ASSOCIATED WITH IMPROVED PROGNOSIS IN GLIOBLASTOMA PATIENTS - Ivan, Michael E (Neuro Oncol, 2017)
INTRODUCTION: Significant racial and social disparities have previously been identified in outcomes from glioblastoma. Although some epidemiologic studies have shown Hispanic ethnicity to be protective, other studies have not replicated this finding. As many studies do not consider race separately from ethnicity, the role of Hispanic ethnicity in glioblastoma survival is not well understood. Florida has one of the largest Hispanic populations in the United States. Using a population-based cancer database, this study examines sociodemographic and survival disparities in glioblastoma patients. METHODS: Data from the Florida Cancer Data System(FCDS) and the US Census were linked for adult (>18yrs) glioblastoma patients to determine disease burden and survival. A multivariable Cox regression model was used to model patient survival adjusting for sociodemographic, tumor, age, surgical resection, adjuvant therapy and clinical characteristics. Adjusted hazard ratios(aHR) and 95% confidence intervals (95% CI) were calculated for overall sample. All statistical analyses were completed with SAS v.9.4. RESULTS: In total, 16,180 Florida adults were diagnosed with glioblastoma between 1981 and 2013. The majority were male (56.0%) and white (93.0%), and 11.2% of glioblastoma patients identified as Hispanic with 2.4% self-identifying as Cuban. Hispanics had significantly better survival compared to non-Hispanics (aHR 0.84; 95% CI 0.78–0.90). Current smokers fared significantly worse (aHR 1.11; 95% CI 1.04–1.18). Higher socioeconomic status was also associated with increased survival (aHR 0.91, 95% CI 0.84–0.99). Younger age at diagnosis, surgical resection, chemotherapy, radiation therapy, and female sex were also associated with significantly improved outcomes. CONCLUSIONS: This study demonstrates clear sociodemographic and survival disparities for glioblastoma patients. This analysis considers race and ethnicity as two distinct variables and shows improved survival outcomes for Hispanic patients. Additionally, patients from neighborhoods with higher socioeconomic status have increased survival. Further analysis is needed to assess the role of histologic and molecular subtypes in these ethnic groups.